Pengaruh Jenis Kemasan dan Suhu Ruang Simpan terhadap Viabilitas Benih Sorgum (Sorghum bicolor [L.] Moench) - Nurisma, Immas; Agustiansyah, Agustiansyah; Kamal, Muhammad (Jurnal Penelitian Pertanian Terapan, 2015)
This study aims to determine: (1) in response to the type of packaging savings and sorghum seed viability; (2) in response to the storage room temperature sorghum seed viability; (3) a combination of types of packaging store and storage room temperature for sorghum seed viability. The research was conducted in October 2013 to January 2014 at the Laboratory of Seed and Plant Breeding, Faculty of Agriculture, University of Lampung. This research is compiled using a completely randomized design with four replications. The design of the treatment applied is factorial (4x3) by the first factor is the type of packaging and the second factor is the temperature store room. Homogeneity of variance between treatments was tested by Bartlett test. Separation of median is done by using the test Least Significant Difference (LSD) at level ? of 5%. The results showed that the seeds of sorghum were packed with cans stored at refrigerator temperature (4 ° C) have the ability better than a plastic jar packaging, cloth flour, and plastic at room temperature (32 ° C) and air conditioning (22 ° C), in maintaining sorghum seed viability after being stored for 4 months. Keywords : Type Packaging, Temperature Storage Room, Sorghum Seed Viability